Preliminary report on the analysis of the stresses in a die-bolster combination - Oxley, P. L. B.; Welsh, M. J. M. (College of Aeronautics, 1964)
An analysis is presented of the stresses in a carbide die-steel bolster combination. Results from a computer treatment of this analysis are given in tabular and graphical form. Suggestions are made as to the choice of interface diameters, and a nomogram is drawn enabling the maximum allowable interference to be selected.